A Prospective Study to Correlate CRP Levels with Incidence of Liver Injury in Dengue Fever in A tertiary care centre amongst Indian population Demographic - Radhakrishnan, Arvind; Rao, V R Mohan (Journal of Neonatal Surgery, 2025)
Background: Dengue fever remains a significant public health issue in India, with liver injury being a common complication. C-reactive protein (CRP), an acute-phase inflammatory biomarker, may have potential utility in predicting hepatic involvement in dengue. This study aimed to assess the correlation between CRP levels and liver injury in patients with dengue fever. Methods: This prospective study was conducted at a tertiary care center and included 25 patients diagnosed with dengue fever (IgM or NS1-positive by ELISA). All patients underwent CRP testing and liver function tests (LFTs). Liver injury was defined as an elevation of AST and ALT levels above 49 U/L. Patients were categorized into CRP-reactive and CRP-non-reactive groups for analysis. Results: Of the 25 patients, 14 were male and 11 were female. Twelve patients were CRP-reactive, while 13 were CRP-non-reactive. Liver injury was observed in 9 patients. Among the CRP-reactive group, 7 patients (58.3%) had elevated AST and ALT levels, whereas only 2 patients (15.4%) in the CRP-non-reactive group showed such elevations. This indicates a higher incidence of liver injury among CRP-reactive patients. Conclusion: The study suggests that elevated CRP levels are associated with a higher incidence of liver injury in dengue fever, indicating its potential as an early predictive marker for hepatic involvement. Further studies with larger sample sizes are warranted to validate these findings and to elucidate the underlying pathophysiological mechanisms